2014
DOI: 10.4018/ijkss.2014070105
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Knowledge Sharing Behaviour among Academics in United Arab Emirates

Abstract: The main objectives of this research are to (i)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…The result is consistent with the outcome of the study of Muhammed & Zaim (2020) that found that leaders' supports are fundamental in knowledge sharing behaviour, which in turn would lead to increased performance. The result confirms the position of Skaik and Othman (2014) that management support is critical towards driving knowledge sharing that would lead to increased competitiveness for an organisation.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The result is consistent with the outcome of the study of Muhammed & Zaim (2020) that found that leaders' supports are fundamental in knowledge sharing behaviour, which in turn would lead to increased performance. The result confirms the position of Skaik and Othman (2014) that management support is critical towards driving knowledge sharing that would lead to increased competitiveness for an organisation.…”
Section: Discussionsupporting
confidence: 77%
“…Organisations' work structure has been found to be fundamental to knowledge sharing (Hall, 2001;Karim & Majid, 2018;Xue et al, 2011). Effective knowledge sharing is only possible when there is a smooth flow of interaction among employee's in the organisation (Skaik & Othman, 2014). Knowledge sharing has been proven to be possible in a work design that allows for sharing (Foss et al, 2009;Karim & Majid, 2018).…”
Section: Relationship Between Work Design and Competitivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…The way of learning, working culture, willingness to share and take chances to share knowledge, play a very important part in improving the knowledge among academic staff in public universities (Sohail, 2009). To create and maintain a knowledge sharing culture in universities, the management should provide the employees with necessary tools and work environment which encourages knowledge sharing (Skaik, 2014). The Deans and Head of departments in universities should keep in mind intrinsic rewards when formulating reward policies (Jahani, 2011) as there is a positive relationship between knowledge sharing and rewards attached to it (Bartol, 2000).…”
Section: Knowledge Sharingmentioning
confidence: 99%